1:1 binary complexes of citric acid with some metal ions: Stability and thermodynamic parameters - (:unkn) unknown (Freund Publishing House Ltd, 2007)
The stability constants of the 1:1 binary complexes of citric acid with Cu2+, Ni2+, Co2+, Mn2+ and Ce 3+ were determined potentiometrically at 15.0, 25.0, and 35.0°C and at an ionic strength of 0.10 mol L-1 (NaClO4). UV-VIS spectroscopic studies were also performed in order to confirm the complexes formation and the stability constants of Cu-citric acid system determined potentiometrically. The thermodynamic parameters, ΔG°, ΔH°, and ΔS° were reported for the complexes formation reactions. The enthalpy and entropy changes of all binary complexes are positive.